2002
DOI: 10.1110/ps.3820102
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability measurements on multimeric proteins using a new H/D exchange‐ and matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry‐based method

Abstract: We recently reported on a new H/D exchange-and matrix-assisted laser desorption/ionization (MALDI) mass spectrometry-based technique, termed SUPREX, that removes several important limitations associated with measuring the thermodynamic stability of proteins. In contrast to conventional spectroscopy-based techniques for characterizing the equilibrium unfolding behavior of proteins, SUPREX is amenable to the thermodynamic analysis of both purified and unpurified proteins using mg to ng quantities of material. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
(49 reference statements)
2
39
0
Order By: Relevance
“…Only very recently has it been shown that the analysis of isotopically labeled proteins by MALDI‐MS represents a viable alternative to ESI‐MS (Henry, 1998; Mandell, Falick, & Komives, 1998). Following this discovery, MALDI‐MS has quickly become a standard tool for folding experiments carried out under equilibrium conditions (Figueroa & Russell, 1999; Ghaemmaghami, Fitzgerald, & Oas, 2000; Powell & Fitzgerald, 2001; Powell, Wales, & Fitzgerald, 2002). However, so far all MS‐based studies on short‐lived folding intermediates have exclusively employed ESI‐MS.…”
Section: Discussionmentioning
confidence: 99%
“…Only very recently has it been shown that the analysis of isotopically labeled proteins by MALDI‐MS represents a viable alternative to ESI‐MS (Henry, 1998; Mandell, Falick, & Komives, 1998). Following this discovery, MALDI‐MS has quickly become a standard tool for folding experiments carried out under equilibrium conditions (Figueroa & Russell, 1999; Ghaemmaghami, Fitzgerald, & Oas, 2000; Powell & Fitzgerald, 2001; Powell, Wales, & Fitzgerald, 2002). However, so far all MS‐based studies on short‐lived folding intermediates have exclusively employed ESI‐MS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of protein equilibrium unfolding induced by chaotropes usually require extensive sample clean-up and thus cannot be carried out ''on-line,'' although Powell et al have managed successfully to measure protein stability by urea-induced unfolding with HDX MALDI MS (Powell & Fitzgerald, 2001;Powell, Wales, & Fitzgerald, 2002). Thermal denaturation is another way to study protein equilibrium unfolding that can be implemented with an ''on-line'' experimental set-up, as demonstrated by the Deinzer group (Maier, Schimerlik, & Deinzer, 1999).…”
Section: B Characterization Of Equilibrium Intermediates In Unfoldinmentioning
confidence: 99%
“…Both H/D exchange with mass spectrometry [13][14][15][16][17][18] and native electrospray mass spectrometry 19 have been successfully applied for the study of protein folding. H/D exchange allows monitoring phase transition (unfolding), and the measuring of the specific kinetics as unfolding processes heralds itself in the appearance of EX1 exchange pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, dimer interchange assays, such as one we have developed here, do provide this type of information. Although study of non-labeled proteins would not be of help with this type of analysis (as dissociated/re-associated dimers are not discernable from never-dissociated dimers), 15 N-labeled proteins allowed us to monitor the dynamics of dimer dissociation. Upon dissociation, normoisotopic and 15 N-labeled monomers re-associate randomly with the formation of heterodimers, and by measuring the area under each of the mass spectrometric peaks, we were able to quantify the rate of dimer dissociation.…”
Section: Discussionmentioning
confidence: 99%